Psychology Students' Perceptions of COVID-19 in a Death Education Course - Testoni, Ines; Iacona, Erika; Corso, Cecilia; Pompele, Sara; Dal Corso, Laura; Orkibi, Hod; Wieser, Michael Alexander (Frontiers in Public Health, 2021)
The systematic removal of death from social life in the West has exposed people living in areas affected by COVID-19 to the risk of being unable to adequately manage the anxiety caused by mortality salience. Death education is a type of intervention that helps people manage their fear of death by offering them effective strategies to deal with loss and anxiety. To that end, a path of death education has been carried out with university students of psychology. The main purpose of the research is to understand how students who participated in the death education course perceive the lockdown experience in light of course teachings. The research was carried out at a university in northern Italy in an area severely affected by COVID-19, during the first year of the pandemic. The group of participants included 38 students, 30 women and 8 men, with an average age of 25.45 years (SD = 7). At the end of the course, the students could respond on an optional basis to the request to comment on the training experience according to what they experienced during the pandemic. A thematic analysis was subsequently carried out on the texts, which made it possible to identify the most relevant thematic areas for the students. The qualitative analyses permitted recognition of three main forms of discovery: the removal of death in contemporary culture; the importance of community, ritual and funeral, and spirituality; and the significance of death education for future health professionals. The texts have highlighted how the removal of these issues exposes people to the risk of being unable to handle extremely painful events such as those related to dying. The results show the positivity of death education pathways conducted at the university level to help students reflect on these issues and manage the related anguish.